Higher VO2max is associated with thicker cortex and lower grey matter blood flow in older adults - Gaia Olivo (Nature Portfolio, 2021)
Abstract VO2max (maximal oxygen consumption), a validated measure of aerobic fitness, has been associated with better cerebral artery compliance and measures of brain morphology, such as higher cortical thickness (CT) in frontal, temporal and cingular cortices, and larger grey matter volume (GMV) of the middle temporal gyrus, hippocampus, orbitofrontal cortex and cingulate cortex. Single sessions of physical exercise can promptly enhance cognitive performance and brain activity during executive tasks. However, the immediate effects of exercise on macro-scale properties of the brain’s grey matter remain unclear. We investigated the impact of one session of moderate-intensity physical exercise, compared with rest, on grey matter volume, cortical thickness, working memory performance, and task-related brain activity in older adults. Cross-sectional associations between brain measures and VO2max were also tested. Exercise did not induce statistically significant changes in brain activity, grey matter volume, or cortical thickness. Cardiovascular fitness, measured by VO2max, was associated with lower grey matter blood flow in the left hippocampus and thicker cortex in the left superior temporal gyrus. Cortical thickness was reduced at post-test independent of exercise/rest. Our findings support that (1) fitter individuals may need lower grey matter blood flow to meet metabolic oxygen demand, and (2) have thicker cortex.